DROP SHIPPING IN ISLAMIC ECONOMIC LAW PERSPECTIVE: E-COMMERCE STUDY INTER MARKETPLACE DROP SHIP IN THE INDUSTRIAL REVOLUTION ERA 4.0 - Rasidin, Mhd.; Sidqi, Imaro; Witro, Doli (Nurani, 2020)
Drop shipping is a business carried out by someone as an intermediary between suppliers and customers. This business has become a big trend in the market because it has the potential to get massive profits. However, there is still an assumption that the business is not following the teachings of Islam. This research will discuss the concept of drop ship in general and the latest drop ship that becomes the current market trend, namely drop shipper between marketplaces is. This study uses qualitative research methods that are literature research. The discussion of this research will focus on normative-juridical studies given Sharia Economic Law. This research is expected to be opened insight for the drop shipper so that the profits and success of his business will be blessed by Allah s.w.t. After the data is collected, it is then analyzed using data analysis techniques, namely data reduction, data presentation, and concluding. The results showed that the drop ship business between marketplaces did not conflict with Islamic teachings, meaning that the business was following the Sharia economic agreements. The business is legal and religiously legal in the State of Indonesia. Therefore, the community must understand the business from management, systems, and payments to be following existing contracts. If the business continues to be developed, it will become a superior and growing halal business in the world. Keywords: Drop ship, E-Commerce, Marketplace, Sharia Economic Law